Karakteristik Pembakaran Difusi Campuran Biodiesel Minyak Jarak Pagar – Etanol / Metanol Pada Mini Glass Tube Dan Mini Copper Tube - M. Arsad Al Banjari; Lilis Yuliati; Achmad As'ad Sonief (ROTOR, 2015)
Diffusion is performed combustion in diesel engines, biodiesel as a biofuel that is used to replace fossil fuels. Many studies have looked at the effects of a mixture of biodiesel fuel ethanol-methanol-diesel with different percentages in terms of engine performance and exhaust emissions, but have never done research on combustion characteristics. This paper discusses how the mix ratio diffusion combustion characteristics of biodiesel - ethanol / methanol on a mini glass tube burner and a mini copper tube burner. the results showed that the use of mini glass tube burner produces more explosions flame than mini copper tube burner. This is because the temperature of the mini copper tube is higher than the temperature of the mini glass tube, and fire explosion occurred because of thecohesionof theglasstubeto thefuel, so that theliquid fueloftenjumpoutofthe burner tipand thenthere was an explosionof fire, and alsocoolingthe fuelvaporwhen passing theminiglasstube. The lower of viscosity and boiling point properties can reduce explosion flame, and making the evaporationfuelmore better. Conclusion, the use ofmini copper tube burner, producesmore stable flamethanmini glass tube burner. and properties of biodiesel-methanol is better than biodiesel-ethanol. Keywords :Biodiesel, diffusion flame, combustion characteristics, mini glass tube burner, mini copper tube burner.